BIM for Energy Modelling of Green Buildings - Al-Haidary, Haidar E. (2018)
A Master of Science thesis in Civil Engineering by Haidar E. Al-Haidary entitled, “BIM for Energy Modelling of Green Buildings”, submitted in November 2018. Thesis advisor is Dr. Adil K. Tamimi. Soft and hard copy available.